Human rights overreach? - Farahat, Anuscheh; Leijten, Ingrid (Netherlands Quarterly of Human Rights, 2022)
Current and future challenges are in need of an effective human rights response. In ensuring this, the question can be asked whether there is such a thing as human rights overreach, and if so, what must be done about it. This contribution deals with this question by, first, outlining various forms of human rights proliferation. For example, proliferation can take the shape of expanding the scope of rights or inventing new human rights. It then illuminates several lines of criticism that can be found in the literature. These concern issues of legalisation and of judicialisation, as well as the indeterminacy of rights. The articles that together form this Special Issue deal with aspects of proliferation and (potential) overreach from different and original angles. After introducing these, it is concluded that the overreach question is even more complex than it seems and requires careful consideration if we want to make human rights more effective and more resilient.
CRIS-Team WoS Importer:2022-06-10
Keywords: Human Rights; proliferation; overreach; legalisation; indeterminacy; judicialisation